The prevalence of imposter syndrome among neurosurgeons in Europe: An EANS YNC survey - Cesare Zoia; Martin N. Stienen; Ismail Zaed; Grazia Menna; Cristina C. Aldea; Jiri Bartek; Marlies Bauer; Diogo Belo; Evangelos Drosos; Christian F. Freyschlag; Stanislav Kaprovoy; Milan Lepic; et al. (Brain and Spine)
Introduction: Imposter syndrome (IS), characterized by persistent doubts about one's abilities and fear of exposure as a fraud, is a prevalent psychological condition, particularly impacting physicians. In neurosurgery, known for its competitiveness and demands, the prevalence of IS remains high. Research question: Recognizing the limited literature on IS within the neurosurgical community, this European survey aimed to determine its prevalence among young neurosurgeons and identify associated factors. Material and methods: The survey, conducted by the Young Neurosurgeon Committee of the European Association of Neurosurgical Societies, gathered responses from 232 participants. The survey included demographics, the Clance Imposter Phenomenon Survey (CIPS), and an analysis of potential compensatory mechanisms. Results: Nearly 94% of respondents exhibited signs of IS, with the majority experiencing moderate (36.21%) or frequent (40.52%) symptoms. Analyses revealed associations between IS and factors such as level of experience, sex, and board-certification. Discussion and conclusion: The findings suggest a significant prevalence of IS among young neurosurgeons, with notable associations with sex and level of experience. Compensatory mechanisms, such as working hours, article reading, and participation in events, did not show significant correlations with IS. Notably, male sex emerged as an independent protective factor against frequent/intense IS, while reading more than five articles per week was identified as a risk factor. The identification of protective and risk factors, particularly the influence of gender and reading habits, contributes valuable insights for developing targeted interventions to mitigate IS and improve the well-being of neurosurgeons.